Effects of perioperative hydrogen inhalation on brain edema and prognosis in patients with glioma: a single-center, randomized controlled study - Wu, Fan; Liang, Tao; Liu, Yang; Wang, Chenhui; Sun, Yongxing; Wang, Baoguo (Frontiers in Neurology, 2024)
Introduction Brain edema is a life-threatening complication that occurs after glioma surgery. There are no noninvasive and specific treatment methods for brain edema. Hydrogen is an anti-inflammatory and antioxidant gas that has demonstrated therapeutic and preventative effects on several diseases, particularly in the nervous system. This study aimed to determine the therapeutic effects of hydrogen administration on brain edema following glioma surgery and elucidate its mechanism. Methods A single-center, randomized controlled clinical trial of hydrogen inhalation was conducted (China Clinical Trial Registry [ChiCTR-2300074362]). Participants in hydrogen (H) group that inhaled hydrogen experienced quicker alleviation of postoperative brain edema compared with participants in control (C) group that inhaled oxygen. Results The volume of brain edema before discharge was significantly lower in the H group (p < 0.05). Additionally, the regression rate of brain edema was higher in the H group than in the C group, which was statistically significant (p < 0.05). Furthermore, 3 days after surgery, the H group had longer total sleep duration, improved sleep efficiency, shorter sleep latency, and lower numerical rating scale (NRS) scores (p < 0.05). Discussion In conclusion, hydrogen/oxygen inhalation effectively reduced postoperative brain edema in glioma patients. Further research is necessary to understand the underlying mechanisms of hydrogen’s therapeutic effects. Hydrogen is expected to become a new target for future adjuvant therapy for brain edema.